Mataram City Government Regional Asset Management Strategy (With the implementation of the Balanced Scorecard) - Thaariq Ghasyiya, Gabriel (Asian Journal of Social and Humanities, 2024)
This study aims to determine alternative regional asset management strategies in the Mataram City Government with  the Balanced Scorecard approach. The main focus in this study is to introduce the concept of Balanced Scorecard to the Mataram City Government Work Unit in charge of regional asset management. The problems faced in this study include a large number of assets, the potential for regional revenue that is not optimal, demands for improvement of community services, and weak performance and organizational systems of regional asset management agencies. This study uses a mixed approach that combines qualitative and quantitative methods. Primary data collection was carried out through in-depth interviews with 5 expert respondents, participant observation, and distribution of survey questionnaires. Secondary data were obtained through documentation studies. The implementation of this research was carried out at the Mataram City Regional Finance Agency. So that the results of this study are expected to formulate the right strategy for the Mataram City Government in determining regional asset management policies and provide input and suggestions for improving regional asset management to focus more on the vision, mission, and organizational strategy and through the implementation of the Balanced Scorecard It is expected to increase the effectiveness and efficiency of regional asset management, optimize regional revenues, and improve the performance of regional asset management agencies in carrying out government administration activities.